Childhood Obesity: A Potential Key Factor in the Development of Glioblastoma Multiforme - Punya Sachdeva; Shampa Ghosh; Soumya Ghosh; Sungsoo Han; Juni Banerjee; Rakesh Bhaskar; Jitendra Kumar Sinha (Life, 2022)
Glioblastoma multiforme (GBM) is a malignant primary tumor type of the central nervous system (CNS). This type of brain tumor is rare and is responsible for 12–15% of all brain tumors. The typical survival rate of GBM is only 12 to 14 months. GBM has a poor and unsatisfactory prognosis despite advances in research and therapeutic interventions via neurosurgery, radiation, and chemotherapy. The molecular heterogeneity, aggressive nature, and occurrence of drug-resistant cancer stem cells in GB restricts the therapeutic efficacy. Interestingly, the CNS tumors in children are the second most usual and persistent type of solid tumor. Since numerous research studies has shown the association between obesity and cancer, childhood obesity is one of the potential reasons behind the development of CNS tumors, including GBM. Obesity in children has almost reached epidemic rates in both developed and developing countries, harming children’s physical and mental health. Obese children are more likely to face obesity as adults and develop non-communicable diseases such as diabetes and cardiovascular disease as compared to adults with normal weight. However, the actual origin and cause of obesity are difficult to be pointed out, as it is assumed to be a disorder with numerous causes such as environmental factors, lifestyle, and cultural background. In this narrative review article, we discuss the various molecular and genetic drivers of obesity that can be targeted as potential contributing factors to fight the development of GBM in children.